Preparation and Magnetic Properties of Anisotropic (Sm,Pr)Co5/Fe Nanocomposites Particles via Electroless Plating - Shi Wang; Jin-Ming Ma; Yan Chen (Journal of Chemistry)
Anisotropic (Sm,Pr)Co5/Fe nanocomposites particles were prepared by electroless plating iron on the surface of (Sm,Pr)Co5 nanoflakes after being prepared by ball milling for 4 h. A uniform and continuous coating layer was obtained due to the addition of complexing agent and the particle size of the reduced Fe particles was in the range of 10~20 nm. When the nominal addition of Fe was 15 wt%, the nanocomposites show enhanced remnant and saturation magnetization: Mr=53.35 emu/g, Ms=73.08 emu/g compared to the noncoated nanoflakes with Mr=48.52 emu/g, Ms=60.15 emu/g, while the coercivity drops from 10.33 kOe to 8.89 kOe. The effect of Fe content on the magnetic properties of the magnets is also discussed.